Towards redemption and recovery an analysis of the recovery narratives of students with depression - Basco, Eunice U.; Pinzon, Mary Jannette L. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2019)
Depression is a pervasive mental disorder which affects millions of people worldwide. With respect to its prevalence, this qualitative study aims to provide further understanding on this mental health condition. I situated depression in a rhetorical analysis as I probed into the narratives of people who are experienced it. I specifically employed Kenneth Burke's dramatistic theory as I delved into the manifestations of the stages the guilt-redemption process, specifically (1)guilt, (2)purification, and (3)redemption, in the narratives of the participants. In-depth interviews were used to gather the narratives of six (6) undergraduate students from the University of the Philippines Diliman. The participants are aged 18 to 24 and have been diagnosed with depression and have experienced recovery. Finding show that the participants exhibited rejection of the human situations and hierarchies they were in. This rejection resulted to depression which is the guilt in their narratives. Negative emotions are also present under depression, and I categorized them as sub-guilts. In order to purify themselves from depression, the participants resorted to varying purification methods. In essence, there is no formula when it comes to recovering from depression as it depends on the individual. Nevertheless, all of the narratives of the participants reflect working on their own betterment as in mortification. Constant communication with their respective support groups is also highlighted as a major factor in the recovery of the participants. Their recovery phases translate to the redemption stage. Only the sub-guilts were removed as the participants could not assert that their depression was completely gone, but they nevertheless considered themselves as having experience recovery. Similar to the cycle nature of the dramatistic process, the participants also report instances of relapse.
Thesis (B.A. in Speech Communication)--University of the Philippines Diliman
Includes bibliographical references and appendices.